The effects of gender and age on health related behaviors - Michelmore Janet; Lombard Catherine; Deeks Amanda; Teede Helena (BMC, 2009)
Abstract Background Lifestyle-related diseases, including diabetes, cardiovascular disease, and some cancers represent the greatest global health threat. Greater insight into health needs and beliefs, using broad community samples, is vital to reduce the burden of chronic disease. This study aimed to investigate gender, age, screening practices, health beliefs, and perceived future health needs for healthy ageing. Methods Random probability sampling using self-completion surveys in 1456 adults residing in Australia. Results Screening behaviors were associated with gender and age. Men and women >51 years were more likely (27%) to have screening health checks than those <50 years (2%). Factors nominated to influence health were lifestyle (92%), relationships (82%), and environment (80%). Women were more likely to nominate preparedness to have an annual health check, willingness to seek advice from their medical practitioner and to attend education sessions. Numerous health fears were associated with ageing, however participants were more likely to have a financial (72%) rather than a health plan (42%). More women and participants >51 years wanted information regarding illness prevention than men or those aged <30 years. Conclusion Age and gender are associated with health related behaviors. Optimal health is perceived as a priority, yet often this perception is not translated into preventative action. These findings will inform future research and policy makers as we strive towards a healthier ageing society and the prevention of chronic disease.